Controlled Vocabulary and Indigenous Terminology in Canadian Arctic Legal Research - Hoffman, Nadine (Libraries and Cultural Resources, 2019)
Accepted manuscript for Hoffman, N. (2020). Controlled vocabulary and indigenous terminology in Canadian Arctic Legal Research. In S. Acadia & M. T. Fjellestad (Eds.), Library and Information Studies for Arctic Social Sciences and Humanities (pp. 110-132). New York: Routledge. 10.4324/9780429504778-4 An earlier version of this chapter was presented at the 9th International Congress of Arctic Social Sciences (ICASS-IX), 8-12 June 2017, Umeå, Sweden. The presentation has been archived in the University of Calgary repository at: https://prism.ucalgary.ca/handle/1880/52147. Cataloguers apply subject headings at the time they catalogue an item. As such, newer, contemporary terms used now to describe Indigenous Peoples and cultures differ from older, historical terminology of the past. This chapter analyses appropriate contemporary and historical controlled vocabulary including Canadian Subject Headings (CSH) and indexes for case law from 1892, as well as the legal literature indexes used in Canadian legal research. Changes in library subject headings and legal index taxonomy reflect changes in social norms, database practices, legal definitions, and various jurisdictions of Indigenous Peoples, including those located in Arctic Canada. Vernacular changes for subject headings were faster to shift for the collective term describing Indigenous Peoples in Arctic Canada, Inuit who were originally called Eskimo, when compared with other Aboriginal populations, notably First Nations, originally called Indian, and Métis. Contemporary researchers of Inuit Peoples and culture are encouraged to adapt search strategies that reflect both historical and contemporary terminology to effectively retrieve relevant database results across time even when outdated search terms must be used.